Comparison of Highly Sensitive CRP and Serum Creatinine as an Early Marker of Renal Impairment - Yeasmin, Roksana; Bhuiyan, Md Nizamul Hoque; Parveen, Sultana; Ferdous, Shamim Ara; Nahar, Nazmun (Journal of Medicine, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> A case control study was done during the period of July 2004 to 2005. The study was carried out in the Department of Biochemistry, Dhaka Medical College, Dhaka. 50 diagnosed chronic renal failure patients of both sexes not yet treated by dialysis and 50 age and sex matched healthy subjects were included in the study as case (Group-II) and control (Group-I) respectively. In this study, mean serum HS CRP concentration of CRF patients (50.938 Â±38.88)mg/l found to be significantly elevated in comparison to control (1.12Â±.29mg/l). In CRF patients, serum HS CRP found to show a strong negative correlation with creatinine clearance and a strong positive correlation with blood urea, serum creatinine. This study shows an inverse linear relationship between HS CRP and CCRin contrast to the inverse curvilinear relationship found to exist between serum creatinine and creatinine clearance. Regression analysis between CCR and HS CRP shows a rise of HS CRP Y one unit (mg/l) is accompanied by creatinine clearance to be decreased by 0 .44ml/min. Mean serum HS CRP concentration in chronic renal failure increases significantly. Early phase of decreased CCR can not be detected by the serum creatinine because serum creatinine does not increase until there is significant fall ( 30 ml/min) of creatinine clearance. In contrast to this serum HS CRP begins to rise from the very beginning of the fall of creatinine clearance. So the early phase of decreased creatinine clearance could be detected by simultaneous rise of serum HS CRP. Key Words: HS CRP, CRF, CCR. Â Â Â DOI = 10.3329/jom.v7i1.1356 J MEDICINE 2006; 7 : 10-14